The gut-lung axis in influenza A: the role of gut microbiota in immune balance - Ou, Guosen; Xu, Huachong; Wu, Jialin; Wang, Shiqi; Chen, Yaokang; Deng, Li; Chen, Xiaoyin (Frontiers in Immunology, 2023)
Influenza A, the most common subtype, induces 3 to 5 million severe infections and 250,000 to 500,000 deaths each year. Vaccination is traditionally considered to be the best way to prevent influenza A. Yet because the Influenza A virus (IAV) is highly susceptible to antigenic drift and Antigenic shift, and because of the lag in vaccine production, this poses a significant challenge to vaccine effectiveness. Additionally, much information about the resistance of antiviral drugs, such as Oseltamivir and Baloxavir, has been reported. Therefore, the search for alternative therapies in the treatment of influenza is warranted. Recent studies have found that regulating the gut microbiota (GM) can promote the immune effects of anti-IAV via the gut-lung axis. This includes promoting IAV clearance in the early stages of infection and reducing inflammatory damage in the later stages. In this review, we first review the specific alterations in GM observed in human as well as animal models regarding IAV infection. Then we analyzed the effect of GM on host immunity against IAV, including innate immunity and subsequent adaptive immunity. Finally, our study also summarizes the effects of therapies using probiotics, prebiotics, or herbal medicine in influenza A on intestinal microecological composition and their immunomodulatory effects against IAV.